1997
DOI: 10.1523/jneurosci.17-01-00363.1997
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and Immunocytochemical Evidence for a cGMP-Mediated Inhibition of Subfornical Organ Neurons by Nitric Oxide

Abstract: The activation of neurons in the subfornical organ (SFO) by angiotensin II (AngII) is well established and is widely regarded as the basis for the AngII-induced increase in water intake. Application of the nitric oxide (NO) donor sodium nitroprusside (SNP) led to an inhibition of the spontaneous electrical activity in 96% of the neurons sensitive for SNP (n = 50). In addition, the firing rate in 60% of the neurons inhibited by SNP decreased in response to superfusion with the natural substrate of the NO syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…Several investigators have shown that Ang II can directly stimulate neurons in the SFO (19,25), and we have observed that the great majority of these neurons were also stimulated by relaxin in the perfusion medium. We have not made such recordings from the isolated OVLT, but in view of the relaxin binding present in this site (10), to which circulating relaxin should have access, it seems likely that relaxin also acts directly on neurons in the OVLT to stimulate neuronal activity there.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Several investigators have shown that Ang II can directly stimulate neurons in the SFO (19,25), and we have observed that the great majority of these neurons were also stimulated by relaxin in the perfusion medium. We have not made such recordings from the isolated OVLT, but in view of the relaxin binding present in this site (10), to which circulating relaxin should have access, it seems likely that relaxin also acts directly on neurons in the OVLT to stimulate neuronal activity there.…”
Section: Discussionmentioning
confidence: 50%
“…Temperature was held constant at 37°C by a Peltier element. Extracellular recordings were made from SFO neurons by using glass-coated platinum-iridium electrodes as described (19). The SFO could be identified easily by its protrusion into the third ventricle and the lateral blood vessels lining the organ on both sides.…”
Section: Immunohistochemical Detection Of Fos In Rat Brain Resulting mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it has been shown that direct application of the NO-donor sodium nitroprusside (SNP) reduces AngII-induced water-intake (Nicolaidis and Fitzsimons, 1975) and inhibits the majority of AngII-sensitive SFO-neurons in an in vitro slice preparation (Rauch et al, 1997). Endogenous NO, which is produced by the neuronal NO-synthase (NOS) and released within the SFO (Jurzak et al, 1994b;Rauch et al, 1997) exerts its inhibitory effect most likely by stimulating the soluble guanylyl-cyclase, as indicated by the increase in cGMP after stimulation with different NO-donors and by the inhibitory effect of mem-brane-permeable 8Br-cGMP on neuronal activity (Rauch et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…NO may play one or more different roles in such neurons. In many spontaneously-firing neuron types, NO may directly modulate firing rate [Pehl and Schmid, 1997;Rauch et al, 1997;Kobayashi et al, 2000;Smith and Otis, 2003]. Another possible role is in protecting rapidly firing neurons from damage due to hyperactivity.…”
Section: Discussionmentioning
confidence: 99%